2012
DOI: 10.1186/1471-244x-12-6
|View full text |Cite
|
Sign up to set email alerts
|

Depression and anxiety in patients with rheumatoid arthritis: prevalence rates based on a comparison of the Depression, Anxiety and Stress Scale (DASS) and the hospital, Anxiety and Depression Scale (HADS)

Abstract: BackgroundWhile it is recognised that depression is prevalent in Rheumatoid Arthritis (RA), recent studies have also highlighted significant levels of anxiety in RA patients. This study compared two commonly used scales, the Depression Anxiety and Stress Scale (DASS) and the Hospital Anxiety and Depression Scale (HADS), in relation to their measurement range and cut points to consider the relative prevalence of both constructs, and if prevalence rates may be due to scale-specific case definition.MethodsPatient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

15
164
2
11

Year Published

2012
2012
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 236 publications
(192 citation statements)
references
References 48 publications
15
164
2
11
Order By: Relevance
“…Some additional confounding factors were not possible to control for, as they were not a part of the original program in the early arthritis followup. For example, depression is common in RA 35, and there is a confirmed strong association between pain and depressive symptoms 36. Moreover, several studies have shown that depression and anxiety may impact clinical response to antirheumatic treatment 37.…”
Section: Discussionmentioning
confidence: 99%
“…Some additional confounding factors were not possible to control for, as they were not a part of the original program in the early arthritis followup. For example, depression is common in RA 35, and there is a confirmed strong association between pain and depressive symptoms 36. Moreover, several studies have shown that depression and anxiety may impact clinical response to antirheumatic treatment 37.…”
Section: Discussionmentioning
confidence: 99%
“…Individuals with inflammatory diseases are three to four times more likely to experience depression (Covic et al, 2012;Duivis et al, 2011;Margaretten et al, 2011), patients with major depression have been found to have increased proinflammatory markers (Howren et al, 2009), and an experimental inflammatory challenge (ie, endotoxin-induced inflammation) in an otherwise healthy population can increase depressed mood (Reichenberg et al, 2001). Moreover, recent research suggests that inflammation may contribute to depression, in part, by altering social experience.…”
Section: Introductionmentioning
confidence: 99%
“…A nursing clinic, specialized in newly diagnosed RA patients, underlined the importance of patients receiving support for their feelings, such as frustration and fear of the future [32]. Investigating psychological well-being [10][11] and emotions [33] in relation to RA is necessary to begin to understand what type of interventions patients can benefit from, and to develop interventions based on patients' experiences of everyday life situations.…”
Section: Discussionmentioning
confidence: 99%
“…In spite of significant advances in drug therapy, RA patients still report pain [9], and at least half of all RA patients experience psychological distress such as anxiety and depression [10][11][12]. Studies have shown that psychological distress is a recurrent problem for RA patients and that, unlike disease activity, symptoms of pain, stiffness and functional impairment are significantly associated with levels of psychological distress [12].…”
Section: Introductionmentioning
confidence: 99%